PENGARUH FUNGSI KEPEMIMPINAN, KOMITMEN ORGANISASI DAN MOTIVASI TERHADAP KINERJA PEGAWAI PADA DINAS LINGKUNGAN HIDUP KABUPATEN MUNA - Wa Neni; Sudirman Zaid; Laode Asfahyadin Aliddin; Rachmat Rialdy Hasan (Jurnal Manajemen, Bisnis dan Organisasi (JUMBO), 2022)
The purpose of this research is examine and explain the effect of leadership functions, organizational commitment and work motivation on employee performance. The paradigm of this study is positivist with a quantitative approach. The data was collected in a cross-sectional manner using a questionnaire. The respondents of this study were all employees of the Muna Regency Environmental Service as many as 66 people. The data analysis method used in testing the hypothesis is Multivariate Regression Analysis.The results of the study indicate that the function of leadership, organizational commitment and work motivation have a positive and significant effect together on employee performance. Furthermore, the partial test results of the leadership function proved to have a positive and significant effect on employee performance. High organizational commitment provides a significant contribution to improving employee performance. Then work motivation has a positive and significant effect on employee performance. This means that the better the implementation of the leadership function, organizational commitment and work motivation, the employee's performance will increase significantly. This result is also strengthened by the statement of respondents based on the description of the variables of leadership function, organizational commitment, work motivation and employee performance, the majority of respondents stated that it was good in its implementation.